ISSUES OF DEVELOPMENT OF INTEGRATION PROCESSES IN DOING BUSINESS BETWEEN ENTERPRISES - Ergashev Alizhon Khodzhimamatovich; Mamazhonov Fayzulla Abdusamatovich (Galaxy International Interdisciplinary Research Journal, 2024)
This paper examines the issues of ensuring the balance and sustainability of the national economy, which require increasing the financial stability of the business entities operating in it, which require scientific research on the development of cooperation and integration processes between enterprises. On this basis, this work reveals the specific aspects of the development of integration and cooperative relations between business entities and entrepreneurship in our country, developed scientific proposals and practical recommendations aimed at identifying priority areas of business and business development, business strategies and the development of cooperative and integration relations.